Movement in the Shadow of Sadness: How Physical Activity Supports the Fight Against Depression - Agata Ossolińska; Patrycja Marta; Filip Huzarski; Gabriela Ferfecka; Klaudia Pawełek; Lucyna Stolarska; Magdalena Rosa-Bończak; Natalia Morawiecka; Olivier Carlton; Weronika Kłosowicz (Journal of Education, Health and Sport)
Physical activity plays a critical role in promoting physical and mental health, positively influencing the prevention of non-communicable diseases (NCDs) and enhancing brain function. Research indicates that regular physical exercise, such as aerobic or strength training, aids in the prevention and treatment of mental disorders such as depression, schizophrenia, and Alzheimer’s disease. The biological mechanisms associated with physical activity include improved cerebral blood flow, modulation of neurotransmitter systems, and increased levels of neurotrophic factors like BDNF. Exercise also affects the balance of neurotransmitters, such as serotonin, dopamine, and GABA, contributing to improved mood, cognitive abilities, and quality of life. Additionally, physical effort reduces inflammation and oxidative stress, supporting brain health and countering neurodegenerative processes. Regular moderate exercise is an effective method to prevent central fatigue and enhance the adaptability of the central nervous system. This paper explores the complex impact of physical activity on mental health and cognitive function, emphasizing its vital role in supporting the therapy of neurological and psychiatric disorders.